Development of Local Culture-Based Drama Learning Materials to Enhance English Students Skill in Listening - Silfia, Efa; Munawwaroh, Khidayatul; Aulya, Ninda Dwi; Manalu, Sindi Peronika (Universitas Batanghari Jambi, 2025)
Listening is one of the essential skills in learning English. However, many students struggle to develop strong listening abilities. Several factors contribute to their low performance in this area. This study aimed to address students’ difficulties in mastering listening skills by applying a drama movie reviewing technique. The research used a research and development design, involving 30 students from general conversation classes. Data were gathered through interviews, questionnaires, and listening achievement tests. The findings revealed that students who were taught using the drama movie viewing technique achieved a higher average listening score (81.46). Additionally, the technique contributed 61.8% to the improvement of their listening skills.